Analysis of Entrepreneurial Orientation And Market Orientation Towards Competitive Advantage (Survey on Coffeeshops in Sukabumi City ) - Rositawati, Neng; Komariah, Kokom; Saori, Sopyan (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of entrepreneurial orientation and market orientation on competitive advantage among coffeeshops in Sukabumi City. As the coffee consumption trend continues to rise in Indonesia, coffee shops face increasing competition that demands strategic innovation and market responsiveness to maintain business sustainability and gain a competitive edge. Using a quantitative approach with descriptive and associative methods, data were collected through questionnaires distributed to 42 coffeeshop owners and managers, applying a saturated sampling technique. The research employed multiple linear regression analysis using SPSS v21 software to test the hypothesis. The results show that both entrepreneurial orientation and market orientation are in the high category among coffeeshops in Sukabumi. Furthermore, both variables have a significant and positive effect on competitive advantage. The correlation coefficient indicates a strong relationship (r = 0.866), while the coefficient of determination (R² = 0.750) suggests that 75% of the variance in competitive advantage can be explained by entrepreneurial and market orientation. Partial hypothesis testing (t-test) confirms that both independent variables significantly influence competitive advantage (t-count > t-table). Simultaneously, the F-test also shows significant results (F-count > F-table). The findings imply that coffeeshops with strong entrepreneurial attributes—such as innovation, risk-taking, and proactivity—and market-focused practices—such as customer orientation and competitor awareness—tend to achieve better competitive positioning. This research contributes to strategic management literature and offers practical insights for small business owners in the food and beverage sector to enhance their competitiveness through entrepreneurial and market-driven strategies.